Mechanism for Settlement of International Trade Disputes in the Case of the European Union's Lawsuit Against Indonesia Regarding Nickel Mining - Nusamara, Arlyn Annabel; Virginia, Virginia; Matondang, Matthew Mikha Sebastian (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Nickel, a naturally formed metal element, has a shiny shape and a sparkling white color. On some islands in Indonesia, nickel is still abundantly found, such as in Sulawesi, which is a hub of mining industry, especially in Morowali and North Morowali. Besides, it is also found on several other islands, like Maluku North (Halmahera), Papua, and Kalimantan. In addition, total nickel exports by 2022 rose to $5.97 billion. Following the entry into force of a policy banning the export of crude nickel seeds on January 1, 2020, Indonesian nickle exports have increased. However, the EU opposed the policy and sued Indonesia to the World Trade Organization (WTO) in early 2021. Indonesia was found to have violated article X.1 of the GATT on violation of regulatory transparency obligations, article 3.1 (b) of the Subsidy Agreement and the Contract Act on Prohibited Subsidies, and article XI.1 of GATT concerning export and import bans. The aim of the filed lawsuit is to maintain the balance of international trade and encourage more environmentally friendly mining practices. However, the impact is a decrease in foreign investment in the nickel sector.